A Carboranyl Electrolyte Enabling Highly Reversible Sodium Metal Anodes via a "Fluorine‐Free" SEI. (17th November 2022) - Tomich, Anton W.; Park, Jehee; Son, Seoung‐Bum; Kamphaus, Ethan P.; Lyu, Xingyi; Dogan, Fulya; Carta, Veronica; Gim, Jihyeon; Li, Tao; Cheng, Lei; Lee, Eungje; Lavallo, Vincent; et al.
Abstract: Realization of practical sodium metal batteries (SMBs) is hindered due to lack of compatible electrolyte components, dendrite propagation, and poor understanding of anodic interphasial chemistries. Chemically robust liquid electrolytes that facilitate both favorable sodium metal deposition and a stable solid‐electrolyte interphase (SEI) are ideal to enable sodium metal and anode‐free cells. Herein we present advanced characterization of a novel fluorine‐free electrolyte utilizing the [HCB11 H11 ] 1− anion. Symmetrical Na cells operated with this electrolyte exhibit a remarkably low overpotential of 0.032 V at a current density of 2.0 mA cm −2 and a high coulombic efficiency of 99.5 % in half‐cell configurations. Surface characterization of electrodes post‐operation reveals the absence of dendritic sodium nucleation and a surprisingly stable fluorine‐free SEI. Furthermore, weak ion‐pairing is identified as key towards the successful development of fluorine‐free sodium electrolytes. Abstract : We explore the pairing of a novel non‐fluorine containing carboranyl electrolyte with pure sodium metal anodes which yields highly reversible, dendrite‐free cell cycling. Solid electrolyte interphase characterization and investigation of sodium metal deposition/stripping processes suggests the electrolyte presented herein is a reliable candidate to enable anode‐free cells.